2010
DOI: 10.1007/s13197-010-0096-z
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of wild apricot kernel press cake for extraction of protein isolate

Abstract: The kernels of apricot (Prunus armeniaca) stones are utilized for extraction of oil. The press cake left after extraction of oil was evaluated for preparation of protein isolate for its use in food supplementation. The apricot kernels contained 45-50% oil, 23.6-26.2% protein, 4.2% ash, 5.42% crude fibre, 8.2% carbohydrates and 90 mg HCN/100 g kernels, while press cake obtained after oil extraction contained 34.5% crude protein, which can be utilized for preparation of protein isolates. The method standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 8 publications
1
22
2
Order By: Relevance
“…Under the optimum extraction conditions, which were determined by using MATLAB software, the yield of WP from walnut meal was 721.8 ± 9.2 g kg −1 ( n = 5) and the content of protein was 878.2 g kg −1 . The results were higher than given in the previous report, in which the protein was extracted from the press cake . For the WPH, the yield of AWPH was 939.8 g kg −1 with DH of 32.24% and the yield of TWPH was 913.7 g kg −1 with DH of 17.33%.…”
Section: Resultscontrasting
confidence: 72%
“…Under the optimum extraction conditions, which were determined by using MATLAB software, the yield of WP from walnut meal was 721.8 ± 9.2 g kg −1 ( n = 5) and the content of protein was 878.2 g kg −1 . The results were higher than given in the previous report, in which the protein was extracted from the press cake . For the WPH, the yield of AWPH was 939.8 g kg −1 with DH of 32.24% and the yield of TWPH was 913.7 g kg −1 with DH of 17.33%.…”
Section: Resultscontrasting
confidence: 72%
“…References Proteins Cereals Brewers' spent grain Ultrasonic-assisted extraction [17] Sequential extraction of proteins and arabinoxylans [18] Enzymatic-assisted extraction [19] Oil crops Rapeseed meal Ultrasound-assisted aqueous extraction [20] Sunflower meals Alkaline solubilization and acid precipitation [21] Hazelnuts meal Solvent extraction (water, acetone) [22] Canola meals Alkaline solubilization and acid precipitation (Isoelectric precipitation) [23,24] Electro-activated solutions (non-invasive extraction method) [25] Salt precipitation [24] Palm kernel cake Enzymatic hydrolysis [26] Fruits and vegetable Apricot kernel cake Alkaline solubilization and acid precipitation [27] Polysaccharides Cereals Brewers' spent grain Enzymatic hydrolysis [28] Sequential extraction of proteins and arabinoxylans [18] Acid hydrolysis [29] Fruits and vegetables Citrus peel and apple pomace Subcritical water extraction [30] Orange peel Microwave extraction [31] Lipids Cereals Brewers' spent grain Soxhlet extraction [32] Fruit and vegetables Grape seeds Pressurized carbon dioxide extraction with compressed carbon dioxide as solvent and ethanol as co-solvent [33] Supercritical fluid extraction [34] Polyphenols Cereals Brewers' spent grain Alkaline hydrolysis [35] Oil crops Rapeseed Ultrasound-assisted aqueous extraction [20] Olive by-products Continuous counter-current liquid-liquid extraction [36] Chemical (acid) hydrolysis [37] …”
Section: Extraction Techniquesmentioning
confidence: 99%
“…In this case, before the alkaline extraction of proteins, a pre-step of detoxification is required in order to remove the HCN present in the kernel cake. The obtained isolates had a protein concentration of 68.8% and fairly good functional properties, especially water and oil absorption capacity and foaming properties [27].…”
Section: Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…and can be utilized for preparation of protein isolates/protein concentrates after detoxification. Sharma et al (2010b) reported that the dilution of press cake with water in 1:20 ration (w/v) followed by boiling for 60 min resulted in free flowing slurry with better yield and is recommended for detoxification of press cake. The maximum solubility (87 %) was observed during solubilization at pH 8 followed by coagulation of filtrate at pH 4 which gave highest protein isolate yield (24.3 %) with 71.3 % extraction efficiency.…”
Section: By-product Utilizationmentioning
confidence: 99%